Analysis of the implementation of the Love Curriculum as an effort to improve ecological understanding of Madrasah Tsanawiyah students - Pratama, M. Arifky; Permatasari, Iin; Almortaza, Kiyo Qaishan; Herawati, Emy; Muthia, Farah (CAHAYA PENDIDIKAN, 2025)
This study aims to analyze the implementation of the Love Curriculum as a strategy to enhance ecological understanding among students of Madrasah Tsanawiyah. The research is motivated by the existing gap between students’ ecological knowledge and its practical application in daily life, where learning that focuses primarily on cognitive aspects has not fully succeeded in fostering ecological awareness and attitudes. The research method employed is a qualitative approach with a literature review design, involving the collection, examination, and analysis of various sources related to ecological education, character education, and the Love Curriculum. Data analysis was carried out using descriptive-analytical content analysis to identify the forms of Love Curriculum implementation, the obstacles encountered in its application, and its impact on students’ ecological attitudes. The findings reveal that the implementation of the Love Curriculum is realized through the integration of love values in subject learning, extracurricular activities, teacher role modeling, and school-based programs. The challenges identified include limited teacher understanding, lack of supporting facilities, low student participation, and insufficient support from the social environment. Nevertheless, the application of the Love Curriculum has shown a positive impact in shaping students’ ecological attitudes, both individually, collectively, and affectively.